Estrategia de integración horizontal y su influencia en la estrategia de operaciones de Mibanco, agencia Huamachuco - año 2015 - Cortijo Salinas, Alexander Jhoel (2016)
This thesis has been done in the city of Huamachuco, La Libertad, Peru; Its main objective substantiate how the strategy influences Horizontal Integration Strategy Operations Mibanco, Huamachuco Agency. After reviewing the problematic reality , it has formulated the research question : How Horizontal Integration Strategy has influenced Operations Strategy My Bank Huamachuco Agency - 2015?. To gather data have been taken into account two populations: 2700 36 workers and clients; of them they have obtained samples of 36 workers and 93 clients respectively. It has been revised official documentation on the website of the entity and applied the respective surveys. With the results, and following the scientific method has been carried out the analysis and discussion corresponding coming to demonstrate the validity of the hypothesis which states that: "The Integration Strategy Horizontal, in the form of fusion influences expansively in Operations strategy Mibanco Agency Huamachuco - Year 2015”. Finally, in formulating the conclusions and recommendations, the main conclusion is that the relation of influence of the independent variable on the dependent variable, supported through the Pearson correlation coefficient of 0.723, was demonstrated; On the other hand, through the qualitative analysis of the nature of the indicators of both variables, it is observed that they correspond according to whether they are weaknesses or strengths respectively, and the main recommendation suggests conducting periodic investigations to measure the effectiveness of business strategies, Como Is the case of the Horizontal Integration strategy, and also of the Functional Strategies, as is the case of the Strategy of Operations; And on the basis of the diagnostic results obtained are determined the corrective measures to be taken.